2008
DOI: 10.1515/cclm.2008.125
|View full text |Cite
|
Sign up to set email alerts
|

Alternative antibody for the detection of CA125 antigen: a European multicenter study for the evaluation of the analytical and clinical performance of the Access® OV Monitor assay on the UniCel® DxI 800 Immunoassay System

Abstract: Background: Cancer antigen CA125 is known as a valuable marker for the management of ovarian cancer. Methods: The analytical and clinical performance of the Access OV Monitor Immunoassay System (Beckman Coulter) was evaluated at five different European sites and compared with a reference system, defined as CA125 on the Elecsys System (Roche Diagnostics). Results: Total imprecision (%CV) of the OV Monitor ranged between 3.1% and 8.8%, and inter-laboratory reproducibility between 4.7% and 5.0%. Linearity upon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Importantly, overall AUCs in ROC curves as well as sensitivities at specified cutoffs were comparable to other methods already used in routine diagnostics. 21 Our findings correspond further with current guidelines such as from the NACB that recommend CA 15-3 in breast cancer-though not for diagnosis but for monitoring of advanced disease and postoperative surveillance. 22 Although the application of CEA is still controversially discussed, 22 several studies have shown its importance in, for example, prediction and early detection of disease progression and metastasis.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, overall AUCs in ROC curves as well as sensitivities at specified cutoffs were comparable to other methods already used in routine diagnostics. 21 Our findings correspond further with current guidelines such as from the NACB that recommend CA 15-3 in breast cancer-though not for diagnosis but for monitoring of advanced disease and postoperative surveillance. 22 Although the application of CEA is still controversially discussed, 22 several studies have shown its importance in, for example, prediction and early detection of disease progression and metastasis.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, for CA15-3 the analytical performance was accurate but not optimal and a difference in slope of 20-40% lower concentrations for the applied method was detected (23). Looking at the analytical performance of CA125, excellent correlation and only minimal differences in slopes and intercepts were reported (24). We conclude that analytical challenges and limitations are seen for most different methods applied in the routine measurement of tumor markers.…”
Section: Discussionmentioning
confidence: 88%
“…Liver, kidneys and spleen were weighed for all mice. rather than the traditional OC125 and M11 antibodies for the detection of CA 125 [25,26].…”
Section: Animals and Treatmentsmentioning
confidence: 99%